If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -0.2(v + -8) = 0.3(6v + -8) Reorder the terms: 9 + -0.2(-8 + v) = 0.3(6v + -8) 9 + (-8 * -0.2 + v * -0.2) = 0.3(6v + -8) 9 + (1.6 + -0.2v) = 0.3(6v + -8) Combine like terms: 9 + 1.6 = 10.6 10.6 + -0.2v = 0.3(6v + -8) Reorder the terms: 10.6 + -0.2v = 0.3(-8 + 6v) 10.6 + -0.2v = (-8 * 0.3 + 6v * 0.3) 10.6 + -0.2v = (-2.4 + 1.8v) Solving 10.6 + -0.2v = -2.4 + 1.8v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1.8v' to each side of the equation. 10.6 + -0.2v + -1.8v = -2.4 + 1.8v + -1.8v Combine like terms: -0.2v + -1.8v = -2v 10.6 + -2v = -2.4 + 1.8v + -1.8v Combine like terms: 1.8v + -1.8v = 0.0 10.6 + -2v = -2.4 + 0.0 10.6 + -2v = -2.4 Add '-10.6' to each side of the equation. 10.6 + -10.6 + -2v = -2.4 + -10.6 Combine like terms: 10.6 + -10.6 = 0.0 0.0 + -2v = -2.4 + -10.6 -2v = -2.4 + -10.6 Combine like terms: -2.4 + -10.6 = -13 -2v = -13 Divide each side by '-2'. v = 6.5 Simplifying v = 6.5
| -18x-6x=-5 | | 5x-15x=70 | | -x+12x=-33 | | 4x^2-67x-289=0 | | .08(15)+.4x=.05(36+7x) | | bz+cz+bx+cx= | | 5x-7=23+3x | | -14x=-182 | | -x/4=-6 | | 15=-d+30 | | (3q+2)(9q^2-12q+4)= | | 4a+-3b= | | .3(a-18)=.9a | | x/4=-6 | | 3x+5x+3+4=39 | | ln(4+x^2)=ln(x)+2ln(2) | | 6a-b-2a-2b= | | .2+1.3t-.8t=1-2.1t-.8 | | -1-2x=-15 | | 13x+15=6x+183 | | 3d=36 | | 8z-22=3(3z-11)-z | | -7x-13=57 | | 13x-15=6x+183 | | -3-4x=-7 | | 54=a-25 | | 49-3x=6x+17 | | 2x-(x+2)+3(x-5)=(x+2)+15 | | 4x-10=-42 | | 1+8x-x^2=0 | | 13-10x=29+17x | | z+(15/31)=(-9/31) |